2022
DOI: 10.1097/01.aoa.0000816736.18929.e1
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Meta-Analyses Comparing Direct Laryngoscopy With Videolaryngoscopy

Abstract: medical record, now firmly entrenched (and for the better!) in most of our practices. I spent decades recording my anesthetics on paper and would still feel perfectly comfortable doing so. Ask most trainees today to do that, and they will melt down in angst before your very eyes. It is clear that, for better or worse, newer emerging technologies have consequences on some of our fundamental skills. However, are we becoming "de-skilled" or "super-skilled"? This intriguing proposal has been described by Steven Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…There have been almost 22 systematic reviews and meta-analyses published comparing video laryngoscopy to direct laryngoscopy, and they dealt with different aspects of endotracheal intubation. Downey et al [ 46 ] reported findings of 21 meta-analyses on the comparison of video laryngoscopy versus direct laryngoscopy. A Cochrane review [ 47 ] also dealt with different forms of video laryngoscopy, i.e., Macintosh-style, hyper-angulated, and channeled laryngoscopy versus direct laryngoscopy for endotracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
“…There have been almost 22 systematic reviews and meta-analyses published comparing video laryngoscopy to direct laryngoscopy, and they dealt with different aspects of endotracheal intubation. Downey et al [ 46 ] reported findings of 21 meta-analyses on the comparison of video laryngoscopy versus direct laryngoscopy. A Cochrane review [ 47 ] also dealt with different forms of video laryngoscopy, i.e., Macintosh-style, hyper-angulated, and channeled laryngoscopy versus direct laryngoscopy for endotracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Videolaryngoscopy is a preferred technique for tracheal intubation when direct laryngoscopy has failed [7]. It is recommended that the success of first pass tracheal intubation should be a primary outcome in airway management research, as it is associated with patient morbidity and mortality [6,8]. However, the effectiveness of videolaryngoscopy in some settings is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical factors can make videolaryngoscopy difficult, particularly when inserting the blade into patients with smaller mouths or in the presence of blood, vomitus or other obstacles in the oral cavity (such as tumours or large tongues). While a recent systematic review of 222 studies with 26,149 patients found that videolaryngoscopy of any design is likely to improve first pass tracheal intubation success and glottic view [6], many included studies had limitations including small sample sizes; differences in settings (operating theatre vs. emergency department); exclusion of patients at high risk of pulmonary aspiration; and inclusion of only experienced providers [6,8,11]. Due to the differences in methodological design, it is uncertain whether videolaryngoscopy makes first pass tracheal intubation more likely during RSI.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of different types of videolaryngoscope now exist, which may be broadly categorized as Macintosh-style, hyper-angulated, and channeled [2]. A systematic review of 21 metaanalyses comparing videolaryngoscopy (VL) with direct laryngoscopy (DL) found the majority of meta-analyses examined had grouped together Macintosh-style and hyper-angulated videolaryngoscope blades, which the authors concluded could potentially mislead airway managers in their choice of which videolaryngoscope to employ for a particular patient or scenario [3]. In their editorial on the subject of VL versus DL, Hansel and El-Boghdadly stated that the threshold of evidence required to support the superiority of VL over DL in achieving first-pass success (FPS) had been reached in 2015 [4], before the first Cochrane review on the topic had been published [5] though Hansel and El-Boghdadly did not recommend any particular VL device.…”
mentioning
confidence: 99%